Study on the Impact of Financing Efficiency on Corporate Innovation - Kang, Chao; Siriwattana, Srochinee (International Journal of Development Administration Research, 2025)
The abstract, written in Thai, should present the research objectives, methodology, and findings in a concise manner, providing an overall summary of the paper. It should include all key terms and be brief and precise.China’s shift to an innovation-driven "new normal" is vital as traditional growth factors decline, but its innovation system suffers from low efficiency and a focus on incremental innovation, lagging behind global leaders despite high explored is the mismatch between financial input and innovation impact, which stems from financing constraints and, critically, low financing efficiency the ineffective allocation of capital to high-value innovation.This study aims to develop an integrated framework linking financing efficiency (effective resource allocation) to corporate innovation quality and sustainability in China, providing both theoretical enrichment and practical policy guidance to bridge the gap between national ambition and on-the-ground outcomes. Research Objectives (1) to explore the impact mechanism and empirical effects of financing efficiency on corporate innovation. (2)to investigate the mediating role of financing constraints and supply chain finance in the relationship between financing efficiency and corporate innovation. (3) to examine the heterogeneity in the impact of financing efficiency on corporate innovation across different types of enterprises (including variations in size, ownership structure, and market orientation) and across different regions. (4) to combine both quantitative and qualitative research methods in analyzing the relationship between financing efficiency and innovation, ensuring a comprehensive understanding of the impact mechanisms. (5) To provide theoretical support and practical guidance for policy formulation and corporate decision-making, aiming to enhance the role of financing efficiency in fostering innovation. This study concludes that financing efficiency (specifically pure technical efficiency) is a crucial positive driver of corporate innovation, especially breakthrough innovation, a finding that advances literature by focusing on efficiency of utilization over mere availability. The study reveals a dual-pathway mechanism where improved financing efficiency alleviates financing constraints and enhances supply chain finance, which then boosts innovation. This relationship is regionally heterogeneous, showing a stronger positive impact in less financially developed central and western regions of China.